The value of prognostic and predictive parameters in early-stage lung adenocarcinomas: A comparison between biopsies and resections. (February 2023) - Wolf, J.L.; Trandafir, T.E.; Akram, F.; Andrinopoulou, E.R.; Maat, A.W.P.M.; Mustafa, D.A.M.; Kros, J.M.; Stubbs, A.P.; Dingemans, A.C.; von der Thüsen, J.H.
Highlights: We found fair concordance between biopsies and resections of lung adenocarcinoma. A higher nuclear grade and desmoplasia are found in resection specimens. Presence of a high-grade growth pattern in biopsies is of prognostic relevance. Survival prediction on biopsies shows an acceptable area under the curve. Biopsy assessment may guide the extent of resection in early-stage adenocarcinoma. Abstract: Introduction: Since lung adenocarcinoma (LUAD) biopsies are usually small, it is questionable if their prognostic and predictive information is comparable to what is offered by large resection specimens. This study compares LUAD biopsies and resection specimens for their ability to provide prognostic and predictive parameters. Methods: We selected 187 biopsy specimens with stage I and II LUAD. In 123 cases, subsequent resection specimens were also available. All specimens were evaluated for growth pattern, nuclear grade, fibrosis, inflammation, and genomic alterations. Findings were compared using non-parametric testing for categorical variables. Model performance was assessed using the area under the curve for both biopsies and resection specimens, and overall (OS) and disease-free survival (DFS) was calculated. Results: The overall growth pattern concordance between biopsies and resections was 73.9%. The dominant growth pattern correlated with OS and DFS in resected adenocarcinomas and for high-grade growth pattern in biopsies. Multivariate analysis of biopsy specimens revealed that T2-tumors, N1-status, KRAS mutations and a lack of other driver mutations were associated with poorer survival. Model performance using clinical, histological and genetic data from biopsy specimens for predicting OS and DSF demonstrated an AUC of 0.72 and 0.69, respectively. Conclusions: Our data demonstrated the prognostic relevance of a high-grade growth pattern in biopsy specimens of LUAD. Combining clinical, histological and genetic information in one model demonstrated a suboptimal performance for DFS prediction and good performance for OS prediction. However, for daily practice, more robust (bio)markers are required to predict prognosis and stratify patients for therapy and follow-up.